Incremental Shuttle Walk Test and Body Composition Measures: Useful Predictive Factors For Complications After Oesophago-Gastric Cancer Surgery?. Issue 4 (December 2021) - Siddaiah-Subramanya, Manjunath; Sinha, Yashashwi; Kamarajah, Sivesh K.; Ghoneim, Abdulrahman; Halle-Smith, James; Tan, Benjamin HL
Background: Oesophagogastric cancer resection carries a morbidity, as high as 60%. Better patient selection, not only with regards to clinical stage but also fitness, reduces morbidity, and improves outcome. Assessment of body composition measures in particular sarcopenia and the incremental shuttle walk test (ISWT) are 2 such tools to evaluate patients' fitness. We investigate the usefulness of these 2 tools in predicting post-operative outcomes following oesophagogastric resection. Methods: All patients who underwent oesophagogastric cancer resection between 2017 and 2019 and consented to participate in ISWT were included in the study. Patient demographics, comorbidity profile and distance walked in ISWT were collected from an electronic database kept locally. Body composition measures were calculated using pre-operative staging CT scans. Outcomes assessed included overall complications, major complications (Clavien-Dindo III-V) and overall survival. Results: Sixty-seven patients met the inclusion criteria. Seventy-nine percent of the cohort were males and the median age was 67. The majority had neoadjuvant chemotherapy (85%) and the overall complication rate was 69% with a major complication rate of 34%. There was no difference in complication rates between groups of patients who managed an ISWT distance of >350 m and ≤350 m. Multi-variate analyses showed that total fat index ( P  = .041), myosteatosis (OR: 3.89; 95% CI: 1.04-16.76; P  = .039) and sarcopenic obesity ( P  = .028) were independent predictors of overall complications. The presence of sarcopenic obesity was associated with poorer overall survival ( P  = .047). There was no correlation between skeletal muscle index and ISWT. Conclusion: ISWT does not predict post-operative morbidity following oesophagogastric cancer resection. However, sarcopenic obesity was associated with both higher overall complication rates and decreased overall survival. The assessment of body composition using CT scans is a useful pre-operative assessment tool for prediction of outcomes in patients undergoing oesophagogastric cancer resection